Levan-based nanocarrier system for peptide and protein drug delivery: Optimization and influence of experimental parameters on the nanoparticle characteristics - SEZER, ALİ DEMİR; TOKSOY ÖNER, EBRU (ELSEVIER SCI LTD, 2011)
Microbial levans are biopolymers produced from sucrose-based substrates by a variety of microorganisms. There is very limited information related to the levan-based drug delivery systems. In this study, bovine serum albumin (BSA) encapsulated-levan nanoparticles were prepared using levan produced by a new Halomonas sp. Effects of polymer and BSA concentrations and rotating speed on in vitro characterization of the nanoparticles were investigated. The size of levan nanoparticles, with the surface charges +4.3 mV to +7.6 mV, changed between 200 nm and 537 nm. The encapsulation capacity of the particles changed between 49.3% and 71.3% depending on the levan concentration used in the formulation. The cumulative in vitro release of protein from the particles was shown to be controlled release of BSA. This study affirmed the suitability of levan by Halomonas sp. to be used as a nanocarrier system for potential delivery of macromolecular drugs such as peptides and proteins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Levan; Polysaccharide; Peptide and protein; Nanoparticle; Controlled release; CHITOSAN NANOPARTICLES; CONTROLLED-RELEASE; MICROSPHERES; SPECTROSCOPY; FUCOSPHERE; PULLULAN; POLYMERS; ALGINATE; CARRIERS